Unraveling global malaria incidence and mortality using machine learning and artificial intelligence–driven spatial analysis - Md. Siddikur Rahman; Md. Abu Bokkor Shiddik (Scientific Reports)
Abstract Malaria remains a significant global health concern, contributing to substantial morbidity and mortality worldwide. To inform efforts aimed at alleviating the global malaria burden, this study utilized spatial analysis, advanced machine learning (ML), and explainable AI (XAI) to identify high-risk areas, uncover key determinants, predict disease outcomes, and establish causal relationships. This study analyzed data from 106 countries between 2000 and 2022, sourced from the World Health Organization, World Bank and UNICEF. A high-performance ML classifier, XGBoost, combined with XAI and causal AI (CAI) techniques was employed to evaluate malaria incidence and mortality. Spatial autocorrelation analyses, such as Getis-Ord Gi* and Moran’s I, were utilized to detect significant geographical clusters and hotspots of malaria. In 2022, malaria cases reached 251.75 million, while the peak of malaria-related fatalities occurred in 2020, totaling 99,554. Nigeria recorded the highest malaria incidence (1,332.99 million), followed by the Democratic Republic of the Congo (623.16 million) and India (319.83 million). South Sudan (149,753), Zambia (143,546), and the Central African Republic (124,801) exhibited the highest malaria mortality rates. High-incidence clusters were observed in Benin, Burkina Faso, and Ghana, with substantial mortality clusters in Benin, the Central African Republic, and Liberia. The XGBoost model demonstrated the best predictive performance for malaria incidence and mortality (RMSE = 0.63, r² = 0.93, adjusted r² = 0.92, and MAE = 0.46). The XAI and CAI methodologies identified key determinants of malaria, such as access to basic sanitation, electricity availability, population growth, and the under-5 mortality rate. Our integrated framework, driven by machine learning and artificial intelligence, offers actionable insights for identifying determinants and hotspots of malaria through spatial analysis. The study advocates for the incorporation of AI-driven spatial models into national malaria surveillance systems to facilitate evidence-based and targeted interventions.